2007
DOI: 10.21273/jashs.132.5.619
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity and Phylogenetic Relationships among Plum Germplasm Resources in China Assessed with Inter-simple Sequence Repeat Markers

Abstract: Inter-simple sequence repeat (ISSR) markers were used to evaluate genetic similarity and interrelationship among 104 plum (Prunus L. spp.) and related accessions from the Chinese National Germplasm Repository for Plums and Apricots and the Tianshan Germplasm Repository for Wild Fruit Resources, including six plum species (Prunus salicina Lindl., Prunus simonii Carr., Prunus ussuriensis Kov. et Ko… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 28 publications
1
30
1
Order By: Relevance
“…ISSRs cost less and are easier to use than amplified fragmentlength polymorphisms (AFLPs) and do not require prior knowledge of flanking sequences, like SSRs (Reddy et al, 2002). ISSR markers are thought to be particularly useful for study of closely related individuals that exhibit low levels of polymorphism (Zietkiewicz et al, 1994) and have been applied as a very useful alternative to fingerprinting and genetic analysis in fruit crops including strawberry (Debnath et al, 2008), raspberry (Debnath, 2007a), clematis (Gardner and Hokanson, 2005), and plum (Liu et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…ISSRs cost less and are easier to use than amplified fragmentlength polymorphisms (AFLPs) and do not require prior knowledge of flanking sequences, like SSRs (Reddy et al, 2002). ISSR markers are thought to be particularly useful for study of closely related individuals that exhibit low levels of polymorphism (Zietkiewicz et al, 1994) and have been applied as a very useful alternative to fingerprinting and genetic analysis in fruit crops including strawberry (Debnath et al, 2008), raspberry (Debnath, 2007a), clematis (Gardner and Hokanson, 2005), and plum (Liu et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…This could be explained by possible repeated backcrossing plum-apricot hybrids with plums. However, Liu et al (2007) reported that hybrids of plum and apricot were more similar to apricot than the plum. The difference between the two studies could be explained by the used multiple male parents, which made their genetic background rather complex.…”
Section: Resultsmentioning
confidence: 99%
“…This method has been used in several fruit crops such as olive (Terzopoulos et al, 2005), pistachio (Kafkas et al, 2006), plum (Lisek et al, 2007), citrus (Shahsavar et al, 2007), and mulberry (Vijayan and Chatterjee, 2003;Vijayan et al, 2006aVijayan et al, , 2006b for the purposes of cultivar identification, germplasm characterization, natural population diversity evaluation, phylogenetic relationship analysis, genetic linkage mapping, and marker-assisted selection. The ISSR was also applied in genus Prunus (Goulao et al, 2001;Liu et al, 2007) and showed higher reproducibility and percentage of polymorphism than AFLP (Goulao et al, 2001). In addition, Turkish Prunus genotypes have only been characterized by morphological data so far and, in other words, no comparative studies on the molecular diversity among subgenera and sections in Turkish Prunus had been done.…”
mentioning
confidence: 99%
“…Plums are the fruit of temperate zone, but however they are grown throughout the globe, from the temperate climatic conditions of Ciberia to that of subtropical climatic conditions of the Mediterranean regions [2]. China has taken a lead in the production of plum fruits in the overall world with total annual production of 4,635,600 metric tons [3]. Pakistan has offered 6700 hactares of its total land for producing 56200 tonnes of plum fruits.…”
Section: Introductionmentioning
confidence: 99%